Prison sourcing: 'doing good' or 'good for business'?. Issue 2 (January 2015) - Lacity, Mary; Rottman, Joseph; Carmel, Erran
This teaching case explores the business and ethics of prison sourcing, the practice of training and hiring prisoners to perform work for the private or public sectors. Although most prison employment programs train and hire workers for manual labor, such as furniture building or textiles, some prison employment programs now train and hire inmates to perform low-level Business Process Outsourcing (BPO) services like call center work, data entry, and document preparation. Prison sourcing is highly controversial. Besides the usual concerns about security and quality of work performed by prisoners, the ethical aspects of prison sourcing are hotly debated. Proponents argue prison sourcing is ethical because it defrays the costs of corrections, helps individuals successfully complete their confinement and prepares them to reintegrate into society, benefitting the individuals, their families, communities, and ultimately tax payers. Opponents argue that prison sourcing is a form of slavery, hurts small businesses, and steals jobs from law-abiding citizens. The authors developed this teaching case to allow students to explore these issues. The case is a dramatized version of an actual case study of prisoners performing BPO work for a private sector company.